Micro and macro determinants of public support for market reforms in Eastern Europe - Bernd Hayo (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
This paper looks at public support for the creation of a market economy in Eastern Europe. As a data base, the Central and Eastern Eurobarometers surveys are employed, covering up to 21 countries over a time period of 1990-96 and totalling more than 100000 observations on individuals. The development of support for market reforms is analysed over time and countries. Moreover, in a number of panel regressions, individual and macroeconomic determinants of support for reforms are studied. Apart from the influence of individual characteristics (age, gender, education, income), the only significant and robust aggregate effect is that those countries that are able to keep inflation low get more support for market reforms. Small government budget deficits may also help to strengthen support. Differences in employment, GDP per capita, openness, private sector share and microeconomic transition progress do not show robust effects on people's attitudes towards the creation of a market economy.
Keywords: P1; P2; O52; 330; Economic Reforms; Eastern Europe; Public Support; Transformation; Systemtransformation; Übergangswirtschaft; Public Choice; Öffentliche Meinung; Marktwirtschaft; Schätzun